Biomechanical Characteristics of Comprehensive Ankle Joint Complex between Chronic Ankle Instability (CAI) and Healthy Control - Kim, B. H.; Jeong, H. S.; Lee, I.; Jeon, H. G.; Lee, S. Y. (Korean Journal of Sport Biomechanics, 2021)
Objective: To investigate the static and dynamic analysis of ankle joint complex between subjects with chronic ankle instability (CAI) and healthy controls. Method: A total of 38 subjects and CAI group (N=19) and healthy control (N=19) participated in this first study. Variables that were measured in this study were as follows: 1) Subtalar joint axis inclination and deviation 2) Rearfoot angle 3) Navicular drop test 4) Heel alignment view in alignment analysis. Intra Correlation Coefficient (ICC) is used for reliability. A secondary 17 subjects are recruited including 9 of CAI and healthy for gait analysis between group. Lower extremity sagittal, frontal, and transverse kinematics were measured. All data were analyzed to ensemble curve analysis. Results: 1) There were statistically significant differences in standing rearfoot, navicular drop, heel alignment view, subtalar joint (STJ) inclination and deviation. 2) Only in sagittal, meaningful difference is showed during walking in gait analysis. Conclusion: Morphological problem can affect ankle sprain in aspect of structure with no relation to compensation of neuromuscular.